Intraday stealth trading : Evidence from the Warsaw Stock Exchange - Będowska-Sójka, Barbara (Economics and Business Review, 2014)
The intraday volatility and volume U-shaped pattern is well documented in literature. It describes the common pattern of investor's behaviour on the stock markets: investors trade in the beginning and the end of the day more intensively than at the lunch time. However that pattern does not differentiate between the trades' size and investor characteristics. The stealth trading hypothesis states that informed traders tend to hide their information. There is a need for such behaviour at the time of low volatility and they may achieve this by breaking up their trades into smaller parts. At a time of high volatility informed traders are willing to place large orders because high volatility provides a sufficient camouflage of their information. We examine volatility patterns for small, medium and large trades and consider how the duration between trades and spreads differs between trade-size categories. Our sample consists of data from the Warsaw Stock Exchange, which is organized as an order-driven market. We show that medium-size trades are associated with relatively large cumulative stock price changes, however these results are not robust when liquidity measures and the duration between the consecutive trades are taken into account. (original abstract)